A regioregular polythiophene–fullerene for polymeric solar cells. Issue 25 (10th March 2015) - Lanzi, Massimiliano; Salatelli, Elisabetta; Benelli, Tiziana; Caretti, Daniele; Giorgini, Loris; Di‐Nicola, Francesco Paolo
ABSTRACT In this article, we present the synthesis and characterization of a new thiophenic copolymer bearing the C60 fullerene directly linked to the end of a hexamethylenic side chain. This copolymer was prepared with good yield using a simple and straightforward post‐polymerization functionalization procedure applied on a soluble regioregular polymeric precursor obtained by regiospecific organometallic coupling. Copolymer structural and photophysical properties were investigated by gel permeation chromatography, thermal analysis (DSC and TGA), NMR, IR, UV–Vis, and atomic force spectroscopy. The double‐cable copolymer possesses good solubility in common organic solvents, high filmability, thermal stability, and low segmental aggregation tendency. It was tested as a photoactive layer in a polymeric solar cell showing a power conversion efficiency under 100 mW cm−2 AM 1.5 illumination higher than 4%, more than that of the reference cell made with the conventionally used P3HT/PCBM blend. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42121.